Chemophysical acetylene-sensing mechanisms of Sb2O3/NaWO4-doped WO3 heterointerfaces. Issue 36 (3rd September 2020) - Kotchasak, Nataporn; Inyawilert, Kanittha; Wisitsoraat, Anurat; Tuantranont, Adisorn; Phanichphant, Sukon; Channei, Duangdao; Yordsri, Visittapong; Liewhiran, Chaikarn
Abstract : Sb2 O3 -Loaded NaWO4 -doped WO3 nanorods were fabricated with varying Sb contents from 0 to 2 wt% by precipitation/impregnation methods and their p-type acetylene (C2 H2 ) gas-sensing mechanisms were rigorously analyzed. Abstract : Sb2 O3 -loaded NaWO4 -doped WO3 nanorods were fabricated with varying Sb contents from 0 to 2 wt% by precipitation/impregnation methods and their p-type acetylene (C2 H2 ) gas-sensing mechanisms were rigorously analyzed. Material characterization by X-ray diffraction, X-ray photoelectron spectroscopy, scanning transmission electron microscopy and nitrogen adsorption indicated the construction of short NaWO4 -doped monoclinic WO3 nanorods loaded with very fine Sb2 O3 nanoparticles. The sensors were fabricated by powder pasting and spin coating and their gas-sensing characteristics were evaluated towards 0.08–1.77 vol% C2 H2 at 200–350 °C in dry air. The gas-sensing properties of the NaWO4 -doped WO3 sensor with the optimum Sb content of 1 wt% showed the highest p-type response of ∼250.2 to 1.77 vol% C2 H2, which was more than 20 times as high as that of the unloaded one at the best working temperature of 250 °C. Furthermore, the Sb2 O3 -loaded sensor offered high C2 H2 selectivity against CH4, H2, C3 H6 O, C2 H5 OH, HCHO, CH3 OH, C8 H10, C7 H8, C2 H4 and NO2 . Mechanisms responsible for the observed p-type sensing and response enhancement behaviors were proposed based on the NaWO4 -doped WO3 –Sb2 O3 (p–n) heterointerfaces and catalytic spillover effects. Consequently, the Sb2 O3 -loaded NaWO4 -doped WO3 nanorods have potential as alternative p-type gas sensors for selective and sensitive C2 H2 detection in various industrial applications.